PRASASTI PLUMPUNGAN SEBAGAI IKON BATIK KOTA SALATIGA SERTA DAMPAKNYA BAGI PENINGKATAN EKONOMI DAN PARIWISATA - Widyatwati, Ken (HUMANIKA, 2015)
Javanese society still steeped in culture and mystique there are a lot of myths, one of hich is the myths associated with the presence of legends inscriptions . Inscription Plumpungan and Plumpungan which is the origin story of Salatiga. Salatiga community later made into an icon inscription plumpungan the name ofÂ Â  Batik Plumpungan. Plumpungan batik is batik drawing pattern is a form of inscription Plumpungan. As one of cultural studies, this research is very important because Inscription Plumpungan used as an icon with the name of Salatiga batik â€œBatik Plumpunganâ€. Legends and inscriptions Plumpungan in Salatiga a local cultural heritage that should be preserved and conserved as an effort to increase the cultural richness of Indonesia. The existence of legends and inscription Plumpungan used as a traditional batik icon Salatiga have an impact for the improvement of people's income Salatiga and also support an increase in the arrival of tourists both local, domestic and foreign so salatiga tourism sector in the city has increased. Small industrial centers established Batik Plumpungan together in one container that Joint Business Group. Joint Business Group is a group of batik artisans who make batik and obtain capital loans to both individuals and groups. In addition to their capital loan craftsmen also have no trouble selling the results because the centers adannya Batik buyers usually consists of tourists, both domestic, local directly come to the center of batik.